(untitled) (Bangladesh Journal of Anatomy, 2014)
Context: The structural and functional components of the foot are composed of highly refined interrelated segments which provide a stable base for supporting the body in both load support and shock absorption during standing, running, walking and jumping. The study was aimed to measure the foot of adult Santhal males of Pirganj upazilla, Rangpur to find out to racial characteristics of their own and compare with Bangalee adult males of the same area. Materials and Methods: The study was carried out on 60 (sixty) adult male Santhals and 120 (one hundred and twenty) adult male Bangalees. Foot length, foot breadth and foot height was measured. Foot index was calculated and foot shape was determined. Results: Height, length and breadth of foot were higher in Bangalees than Santhals and showed a significantly higher value for the foot length. Regarding the foot shape, slender foot was found more in Bangalees but most of these two groups have standard foot shape. Conclusion: In the present study significantly higher value of foot length and higher percentage of slender foot in Bangalees but higher percentage of broad foot among the Santhals were found . Slender foot in Bangalees may be due to less weight bearing habit than Santhals. DOI: http://dx.doi.org/10.3329/bja.v11i1.20506 Bangladesh Journal of Anatomy, January 2013, Vol. 11 No. 1 pp 30-33